Detrital zircon U-Pb and Lu-Hf data for a kinzigitic gneiss (Jequitinhonha Complex, Araçuaí Orogen, SE Brazil) constrain the age of a huge storage of Ediacaran carbon. (January 2021) - Pacheco, Fernando Estevão Rodrigues Crincoli; Caxito, Fabrício Andrade; Pedrosa-Soares, Antônio Carlos; Dussin, Ivo Antônio; Gonçalves-Dias, Tatiana
Abstract: The precursor basin of the Araçuaí – West Congo Orogenic System (AWCO) formed a large gulf within the São Francisco – Congo Paleocontinent (SFCP), where sedimentary successions ascribed to the Jequitinhonha Complex and Macaúbas Group were deposited in the Neoproterozoic. This precursor basin system comprises an aborted continental rift of Early Tonian age and a Cryogenian rift that evolved to ocean-floor spreading up to the Early Ediacaran. The Jequitinhonha Complex is an extensive metasedimentary unit located in the northeastern Araçuaí Orogen, consisting of Al-rich paragneiss (kinzigite), sillimanite-graphite gneiss and associated economic deposits of flake graphite, quartzite and lenses of calc-silicate rock, metamorphosed to upper amphibolite or granulite facies around 570–550 Ma. U-Pb (LA-MC-ICP-MS) data of 110 detrital zircon grains from the paleosome of a migmatitic paragneiss yield five main age peaks at 2564 ± 35 Ma (5% of the grains), 2012 ± 21 Ma (7%), 1807 ± 19 Ma (12%), 960 ± 8 Ma (29%) and 662 ± 6 Ma (48%), with the youngest grains around 630–609 Ma, and a major age gap from the Statherian to Stenian. The U-Pb age spectrum coupled with Lu-Hf in zircon (LA-MC-ICP-MS) data for 106 zircon grains suggest the following sources: Neoarchean to Orosirian grains were sourced from the SFCP basement, Early Tonian grains from the anorogenic magmatic province, and Cryogenian to Early Ediacaran grains were provided by the Southern Bahia Alkaline Province and Rio Doce magmatic arc. The εHf(t) values show a predominant contribution from evolved crust, with minor involvement of moderately juvenile crust. The sedimentation of Jequitinhonha Complex protoliths developed from the Cryogenian to Early Ediacaran, partially within anoxic marine environments favorable to the preservation of organic matter that formed the huge graphite deposits and lots of smaller occurrences found in the region, accumulating probably more than one billion tons of raw graphite. The youngest detrital zircon population suggests that the deposition record of the Jequitinhonha Complex covers the Cryogenian continental rifting event followed by the development of oceanic crust to the onset of subduction and building of the Rio Doce magmatic arc in the Early Ediacaran. The regional accumulation and preservation of carbon-rich sediments (now graphite-rich gneiss) most probably represent one of the largest storages of Ediacaran carbon around the world. Highlights: New U-Pb detrital zircon data provide an Ediacaran age for the Jequitinhonha Complex. The Rio Doce Arc is an Ediacaran source for the Jequitinhonha Complex. A Cryogenian source related to alkaline magmatism of the Southern Bahia Alkaline Province. Lu-Hf isotope analysis shows a contribution from recycled sources. Data constrain the burial of organic matter that was metamorphosed into a graphite deposit.